MORPHOLOGICAL AND MOLECULAR DIVERSITY OF SCLEROTINIA SCLEROTIORUM (LIB.) DE BARY ISOLATES OF INDIA - N. MANJUNATHA,; T. PRAMEELA DEVI,; N. PRABHAKARAN,; GURUDEVI V. NAVALI, (The Bioscan, 2014)
Sclerotinia sclerotiorum is most successful soil-inhabiting necrotropic filamentous, ascomycetes fungus with a broad host range of > 400 plant species. The morphological and molecular diversity of 9 isolates of Sclerotinia sclerotiorum collected from different host plants and geographical locations of India were studied by using different morphological and molecular markers. The isolates varied in morphological characters viz., colony growth, growth rate, colony appearance and sclerotia. The growth rate of isolates varied from 0.24mm-1.25mm/ hr and they were grouped as fast, medium and slow growing isolates. Out of 9 isolates only four isolates produced flattened and elongated black coloured sclerotia. Extracted genomic DNA of fungus was quantified by Nano-drop and 550bp size DNA fragment was amplified with ITS primer set. The genomic DNA of fungal isolates showed no variability among the nucleotide sequences of ITS region and more homogeneity was observed with ITS-RFLP. The RAPD and URP-PCR banding pattern were analyzed by UPGMA (NTsys-PC). The dendrograms obtained by cluster analysis revealed that isolates of different geographical locations collected were distinctly diverse.